High-performance field effect transistors from solution processed carbon nanotubes. - Wang, H; Luo, J; Robertson, A; Ito, Y; Yan, W; Lang, V; Zaka, M; Schäffel, F; Rümmeli, M; Briggs, G; Warner, J (2010)
Nanoelectronic field effect transistors (FETs) are produced using solution processed individual carbon nanotubes (CNTs), synthesized by both arc discharge and laser ablation methods. We show that the performance of solution processed FETs approaches that of CVD-grown FETs if the nanotubes have minimal lattice defects and are free from surface contamination. This is achieved by treating the nanotubes to a high-temperature vacuum annealing process and using 1,2-dichloroethane for dispersion. We present CNT FETs with mobilities of up to 3546 cm(2)/(V s), transconductance of 4.22 μS, on-state conductance of 9.35 μS and on/off ratios as high as 10(6). High-resolution transmission electron microscopy is used to examine the presence of catalyst particles and amorphous carbon on the surface and Raman spectroscopy is used to examine the lattice defects, both of which lead to reduced device performance.